Analisis Pengaruh Inflasi, Produk Domestik Bruto (PDB), dan Bank Indonesia Rate (BI Rate) Terhadap Indeks Harga Saham Gabungan (IHSG) di Indonesia Periode 2017-2021 - Arini Mafaza; Nur Diana; Dewi Diah Fakhriyyah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to analyze the effect of inflation, Gross Domestic Product (GDP), and Bank Indonesia Rate (BI Rate) on the Composite Stock Price Index (IHSG) in Indonesia for the period 2017-2021. The independent variables in this study are inflation, gross domestic product, and Bank Indonesia rate, while the dependent variable is the composite stock price index. This research is a correlational research with a quantitative approach. The data used in this study are secondary data obtained from the Bank Indonesia (BI) and Indonesia Stock Exchange (IDX) websites. Sampling using purposive sampling method. The data analysis used is multiple linear regression analysis using SPSS. The results showed that inflation, gross domestic product, and Bank Indonesia rate had a significant effect on the composite stock price index. Inflation has no significant effect on the composite stock price index, gross domestic product and Bank Indonesia rate have a positive and significant effect on the composite stock price index.Keywords: Inflation, gross domestic product, bank indonesia rate, composite stock price index